Capital structure determinants for mining firms in Sub-Saharan Africa - Ntombela, Zamahlobo (My University, 2018)
We use static and dynamic panel data models to determine the capital structure determinants for mining firms in Sub Saharan Africa. Our sample of 50 mining firms was divided into noncross listed firms and firms cross listed on international stock exchanges. Estimation methods which were used for the static models include OLS, FE and RE. For the dynamic model, modern estimation techniques such as sys-GMM were used. Using various measures of leverage, we find that tangibility of assets, firm size, growth prospects, profitability and nondebt tax shields are significant determinants of leverage. We find strong evidence that the Pecking Order Theory also exists for mining firms. Lagged leverage is a significant determinant of capital structure, suggesting that mining firms do indeed adjust their leverage towards an optimal capital structure. Our results show that there are differences in capital structure behaviour between non-cross listed and cross listed mining firms. Where the biggest differences are in financing strategies with regards to short-term debt. We find that non-cross listed firms use more short-term debt than cross listed firms. The impact of the commodity price cycle on capital structure was also investigated. The commodity price cycle is an insignificant determinant of leverage. However, mining firms will issue more debt when the commodity prices are in a boom cycle.
Report submitted in partial fulfillment of the requirements for the degree of Master of Management in Finance and Investment Faculty of Commerce, Law and Management Wits Business School University of the Witwatersrand Johannesburg, South Africa
Keywords: Capital--Africa, Sub-Saharan; Corporations--Africa, Sub-Saharan--Finance